Disturbed craving regulation to gaming cues in internet gaming disorder: Implications for uncontrolled gaming behaviors. (August 2021) - Zhang, Jialin; Chen, Shuaiyu; Jiang, Qing; Dong, Haohao; Zhao, Zhen; Du, Xiaoxia; Dong, Guang-Heng
Abstract: Background: The ability to control craving for games is very important to abstain from Internet gaming disorder (IGD) and abundant clinical evidence has suggested that craving dysregulation is the essential pathogenesis for IGD. However, the neural mechanism underlying this feature remains unclear. Methods: Subjective evaluation and fMRI data from 44 participants (IGD participants: 21; recreational Internet game users (RGUs): 23) were collected while they were performing a regulation of craving task. We analyzed and compared their brain features while they regulated cravings to gaming stimuli. Results: Compared to RGUs, IGD participants showed enhanced brain activation in the right anterior cingulate cortex, posterior cingulate cortex (PCC), orbitofrontal cortex and middle temporal gyrus and in the left dorsolateral prefrontal cortex and thalamus during the regulation of craving task. Generalized psychophysiological interaction (gPPI) analysis revealed that IGD participants showed decreased functional connectivity between the right PCC and right inferior parietal lobule compared to that in RGU participants. Conclusions: The results suggested that deficits of craving regulation in IGD participant were associated with the imbalanced coordination between the reward network and the executive network. Enhanced game-seeking motivation and disturbed executive control are responsible for craving dysregulation in IGD participants. These findings suggest a biological mechanism for IGD that may help in finding potential interventions. Highlights: IGD subjects show abnormal craving-related brain activations during gaming craving regulation. IGD subjects show disturbed executive control over gaming craving. Enhanced game craving and disturbed executive control are responsible for craving dysregulation in IGD participants.